A multidisciplinary research agenda for the acceptance of Golden Rice. Issue 5 (12th September 2016) - Bongoni, Radhika; Basu, Soutrik
Abstract : Purpose: The world is facing serious global food security challenges such as the need for sufficient food for a growing population and an exponential growth in nutrient deficiency disorders. Agricultural biotechnology, such as genetically modified (GM) crops, offers itself as a promising solution to address one or more of these issues. Golden Rice (GR) is an example of a GM crop which contains high amount of β-carotene, a compound which is an antioxidant and a precursor of vitamin A. In spite of GR's promised potential benefits in combating vitamin A deficiency (VAD) disorders it is still not cultivated. This viewpoint paper aims to present the reader with a need for multidisciplinary research agenda, the outcomes of which can contribute towards the acceptance of GR. Design/methodology/approach: This viewpoint paper is based on an extensive literature review to identify the "gaps" which contributed to low acceptance of GR. This paper presents a systematic discussion on the importance of GR in tackling VAD and discusses controversies around GR and a scientific approach to tackle them. Findings: The literature review clearly indicates that there is a huge gap in information substantiating the potential of GR for consumers as well as for the farming community. Addressing these issues can substantially increase the acceptance and cultivation of GR. This viewpoint paper proposes food technologists' and social scientists' research agenda for GR and further indicates how the involvement of other research disciplines can improve the acceptance of GR. Originality/value: The literature review indicates the potential of GR in tackling VAD disorders but clearly lacks information to substantiate these arguments. This paper presents authors' opinions, urging scientists to take up a multidisciplinary research approach to emancipate GR from the clutches of GM food controversies.